2017
DOI: 10.1016/j.gaitpost.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Selective motor control correlates with gait abnormality in children with cerebral palsy

Abstract: Score on SCALE showed a significant negative correlation with GPS (rs = -0.603, p< 0.001). Cerebral injuries in CP result in damage to the motor tracts responsible for SMC. Our results indicate that this damage is also associated with changes in the development of walking pattern in children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 16 publications
(20 reference statements)
5
30
0
Order By: Relevance
“…On the other hand, reduced motor selectivity might also impact on UL movement pathology in children with uCP. The importance of selective motor control for gait performance was recently reported [24], though this area remains unexplored for the UL. Future studies incorporating the assessment of selective motor control, as measured with e.g.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, reduced motor selectivity might also impact on UL movement pathology in children with uCP. The importance of selective motor control for gait performance was recently reported [24], though this area remains unexplored for the UL. Future studies incorporating the assessment of selective motor control, as measured with e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a slow transition from hip and knee extension in terminal stance to hip and knee flexion in initial swing leads reduced foot clearance in swing due to reduced hip and knee flexion. Chruscikowski et al (2017) studied 194 patients with bilateral CP and found a significant, negative correlation between SMC measured using SCALE and gait impairment, as measured by Gait Profile Score, suggesting that impaired SMC negatively affects gait function.…”
Section: Influence Of Neuromuscular Deficits On Gait In Cerebral Palsmentioning
confidence: 99%
“…As the lower extremities and the trunk are involved during walking, knowledge about their individual and combined impact on gait is essential for developing optimal gait-trainingstrategies [3]. Studies exploring the impact of different lower extremity impairments such as spasticity, contractures, muscle weakness, selective voluntary motor control (SVMC)) on functional ambulation and gross motor function in children with CP found that a lack of muscle strength and SVMC were the strongest predictors [4][5][6][7][8][9][10][11]. Spasticity and a decreased range of motion (contractures) of the lower extremities were found to have smaller effect on gait [5,8,10].…”
Section: Main Text Introductionmentioning
confidence: 99%